Vernacular architecture in the Codroy Valley - MacKinnon, Richard Paul, 1957- (Book collections on Project MUSE., 2002)
"Vernacular Architecture in the Codroy Valley is the story of a small Newfoundland community as told through its buildings. From adding on a kitchen to constructing a completely new house, the way people build and change their homes says a great deal about their lives, past and present. Richard MacKinnon's insights into the stories revealed by the buildings of the Codroy Valley will have you looking at the buildings in your own community in a whole new way."--Jacket.